Coping of children with cancer on school removal because of hospitalization - Viviani Viero; Carmem Lúcia Colomé Beck; Paula Hübner Freitas; Alexa Pupiara Flores Coelho; Suzinara Beatriz Soares de Lima; Bruna Parnov Machado (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210956 Aim: to identify coping of the children with cancer on being removed from school life because of hospitalization. Method: research with a qualitative approach, developed in a University Hospital in the state of Rio Grande do Sul, from October to November 2007, with the use of semi structured interviews with nine children and of content analysis. Results: two thematic categories emerged: "Difficulties referred to the child's school performance: of the diagnosis to the treatment" and "Support and stimulus to staying in school", in which it was mentioned the relatives, school of origin and hospital type. Conclusions: thinking about the clashes of these children when across with the removal of the school life is relevant to nursing professionals as also being attention to them, in order to provide comprehensive care to these clients being relevant.